Tindak Tutur Asertif dalam Film Gara-Gara Warisan Sutradara Muhadkly Acho - Nurhaliza, Nurhaliza; Alber, Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study aims to find out, analyze, and interpret the forms of assertive speech acts found in the film because of the legacy of director Muhadkly Acho. The approach in this study uses a qualitative approach with content analysis method. The data collection techniques used are documentation, observing, and note-taking techniques. Data analysis techniques used are data collection, data reduction, data display, and conclusions. The results of this study indicate that the most commonly found assertive speech acts are assertive speech acts of informing with marker indicators conveying news/information. This proves that the use of assertive speech acts, especially telling speeches, is caused by the influence of the character's speech. Every utterance made by the characters in this film cannot be separated from the aspect of communication. The communication is contained in the form of dialogue. The dialogue carried out by the characters in the film conveys information in the form of opinions, thoughts, goals, and feelings either directly or indirectly. As for the least assertive speech act found in the film Gara-Gara Warisan directed by Muhadkly Acho, namely the assertive speech act of boasting with the marker indicator of giving praise/proud. From this statement it shows that assertive speech acts have an effect on the development of linguistics, especially pragmatics which is an important science in learning language according to the context. Without the knowledge of pragmatics, speech acts are difficult to understand for both speakers and speech partners which results in communication not running smoothly. In other words, speech acts are a very important element in pragmatic studies, so this research has implications for the development of linguistics